Waist-to-height ratio and its associations with body mass index in a sample of Tuscan children in primary school - Francesca Santomauro; Chiara Lorini; Francesca Pieralli; Giuditta Niccolai; Paola Picciolli; Stefania Vezzosi; Guglielmo Bonaccorsi (Italian Journal of Pediatrics, 2017)
Abstract Background Visceral obesity in children increases the risk of developing cardiovascular diseases. To evaluate overweight children, in addition to Body Mass Index (BMI), waist-to-height ratio (WHtR) can be used to predict cardiometabolic risk. The goal of this study is to describe WHtR in a sample of Tuscan children. Methods A sample of children living in the province of Pistoia, Tuscany, was measured for the following anthropometric parameters: weight, height, and waist circumference. BMI and WHtR were calculated. For the latter indicator, a threshold of 0.5 was considered as a cardiovascular risk predictor. The subjects were classified into underweight, normal weight, overweight, and obese using Cole’s cut-offs. Results The number of children enrolled were 1575 (821 males; 754 females), aged 6–11 years. Of them, 64.3% were normal weight, 4.9% underweight, 22.3% overweight, and 8.5% obese. Moreover, 12.8% had a WHtR ≥0.5 (85.7% males; 88.7% females). The average WHtR value was 0.45 ± 0.045, and was significantly different as per gender (F = 0.45 vs. M = 0.46). WHtR was significantly correlated with BMI (r = 0.766). Conclusion The average WHtR value was in line with previous studies conducted among children of similar age groups. Large-scale perspective studies are needed to validate the Italian WHtR cut-offs for children.